The Effect of Supplementation of Fish Protein Hydrolysate to the BSF-Based Aquafeed on the Growth, Survival, Fatty Acids, and Histopathology of Juvenile Lobster (Panulirus ornatus) - Ishaaq Saputra; Yih Nin Lee; Ravi Fotedar (Aquaculture Nutrition)
The present study aims to evaluate the effect of liquid fish protein hydrolysate (FPH) following fishmeal substitution with full-fat and defatted BSF (black soldier fly, Hermetia illucens) meal in the feeds of juvenile ornate spiny lobster, Panulirus ornatus. The physiological aspects of juvenile lobsters including growth, fatty acids profile, and histopathology were observed. Six isoenergetic experimental feeds having a protein-to-energy ratio of 26 CP mg kJ−1 were formulated with the substitution of fishmeal at 25% using liquid FPH, full-fat BSF (FBSF), defatted BSF (DBSF), and their combination. The specific growth rate, final body weight, final total length, and length increment of juvenile lobsters (initial weight was 0.21 ± 0.01 g and total length was 20.53 ± 0.12 mm) were significantly affected by the fishmeal substitution (P <0.05) and improved with the addition of liquid FPH in the feeds containing FBSF and DBSF. The whole body proximate analysis showed that the liquid FPH to the feeds containing DBSF increased the ash and protein content significantly (P <0.05). The total monounsaturated fatty acids (∑MUFA), saturated fatty acids (∑SFA), and omega 9 fatty acids (∑n−9 FA) of juvenile lobsters’ whole bodies fed with dietary DBSF and FPH supplementation were significantly higher than those of others (P <0.05). The histopathological analysis indicated that the villus size and the muscle thickness in the intestine were not significantly affected by FPH supplementation. However, the hepatopancreas histopathology indicated the presence of B-cells and R-cells in the juvenile lobsters fed with FPH-supplemented feeds. The present results suggested the supplementation of liquid FPH to the formulated feed with FBSF and DBSF for juvenile lobsters can improve the lobsters’ growth and fatty acids availability.